2009
DOI: 10.1590/s0102-09352009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Uso de morfina, xilazina e meloxicam para o controle da dor pós-operatória em cadelas submetidas à ovariossalpingo-histerectomia

Abstract: Uso de morfina, xilazina e meloxicam para o controle da dor pós-operatória em cadelassubmetidas à ovariossalpingo-histerectomia [Morphine, xylazine and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(3 reference statements)
1
5
1
1
Order By: Relevance
“…Similar findings have been reported after administration of morphine (0.1mg kg -1 ) and sodium chloride (0.9% NaCl) epidurally in bitches resulting in cardiovascular stability (Pereira and Marques, 2009). Lawal and Adetunji (2009) have compared the effects of epidural bupivacaine (1mg kg -1 ), lidocaine (4mg kg -1 ) or lidocaine (0.5mg kg -1 ) combined with bupivacaine (0.5mg kg -1 ) in cats.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar findings have been reported after administration of morphine (0.1mg kg -1 ) and sodium chloride (0.9% NaCl) epidurally in bitches resulting in cardiovascular stability (Pereira and Marques, 2009). Lawal and Adetunji (2009) have compared the effects of epidural bupivacaine (1mg kg -1 ), lidocaine (4mg kg -1 ) or lidocaine (0.5mg kg -1 ) combined with bupivacaine (0.5mg kg -1 ) in cats.…”
Section: Discussionsupporting
confidence: 83%
“…Respiratory variables have been shown to be greatly altered by morphine (Valadão et al, 2002;Silva et al, 2004;Pereira and Marques, 2009), however, our results showed stability of the studied parameters (f R , SpO 2 , FiO 2 e P E´C O 2 ). Yaksh et al (2000) corroborates these results for having observed minimal changes in respiratory variables after epidural administration of morphine at 5mg in 0.9% sodium chloride.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…O conhecimento da topografia do cone medular também é importante para a elaboração de técnicas que permitam acessar de forma segura o espaço epidural, onde será possível utilizar essa via para aplicação, não só de anestésicos, mas também de outros fármacos que necessitem de uma absorção mais lenta e duradoura, como opióides, antiinflamatórios e sedativos (Pereira 2007, Freitas et al 2008, Silva et al 2008.…”
Section: Introductionunclassified
“…However, there were technical difficulties, as to tissue resistance and animal movement for subdermal application, and the animals had to be sedated. Due to the sympatholytic effects of xylazine, sildenafil was not used daily so as not to potentialize systemic vasodilatation and lead to death 14 .…”
Section: Resultsmentioning
confidence: 99%